Gene expression of the liver of vaccination-protected mice in response to early patent infections of Plasmodium chabaudi blood-stage malaria - Saleh Al-Quraishy; Mohamed A. Dkhil; E. M. Al-Shaebi; Abdel-Azeem S. Abdel-Baki; Marcos J. Araúzo-Bravo; Denis Delic; Frank Wunderlich (Malaria Journal, 2018)
Abstract Background The role of the liver for survival of blood-stage malaria is only poorly understood. In experimental blood-stage malaria with Plasmodium chabaudi, protective vaccination induces healing and, thus, survival of otherwise lethal infections. This model is appropriate to study the role of the liver in vaccination-induced survival of blood-stage malaria. Methods Female Balb/c mice were vaccinated with a non-infectious vaccine consisting of plasma membranes isolated in the form of erythrocyte ghosts from P. chabaudi-infected erythrocytes at week 3 and week 1 before infection with P. chabaudi blood-stage malaria. Gene expression microarrays and quantitative real-time PCR were used to investigate the response of the liver, in terms of expression of mRNA and long intergenic non-coding (linc)RNA, to vaccination-induced healing infections and lethal P. chabaudi malaria at early patency on day 4 post infection, when parasitized erythrocytes begin to appear in peripheral blood. Results In vaccination-induced healing infections, 23 genes were identified to be induced in the liver by > tenfold at p < 0.01. More than one-third were genes known to be involved in erythropoiesis, such as Kel, Rhag, Ahsp, Ermap, Slc4a1, Cldn13 Gata1, and Gfi1b. Another group of > tenfold expressed genes include genes involved in natural cytotoxicity, such as those encoding killer cell lectin-like receptors Klrb1a, Klrc3, Klrd1, the natural cytotoxicity-triggering receptor 1 Ncr1, as well as the granzyme B encoding Gzmb. Additionally, a series of genes involved in the control of cell cycle and mitosis were identified: Ccnb1, Cdc25c, Ckap2l were expressed > tenfold only in vaccination-protected mice, and the expression of 22 genes was at least 100% higher in vaccination-protected mice than in non-vaccinated mice. Furthermore, distinct lincRNA species were changed by > threefold in livers of vaccination-protected mice, whereas lethal malaria induced different lincRNAs. Conclusion The present data suggest that protective vaccination accelerates the malaria-induced occurrence of extramedullary erythropoiesis, generation of liver-resident cytotoxic cells, and regeneration from malaria-induced injury in the liver at early patency, which may be critical for final survival of otherwise lethal blood-stage malaria of P. chabaudi.